Islamic Law Perspective of the Practice of Marriage Guardianship in the Karamat Community, Buol Regency - Sakur, Irwan; Nasaruddin, Nasaruddin; Gani Jumaat; Nurkhaerah, Nurkhaerah (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2024)
This study examines the practice of Taukil Wali nikah in the Karamat community, Buol Regency, from the perspective of Islamic law. This phenomenon arises when the lineage guardian, especially the biological father, often delegates the right of guardianship to the penghulu or local religious figure, without going through procedures involving the Religious Affairs Office as regulated in Islamic law. A qualitative approach was used to explore the background, process, and perceptions of the community regarding this practice more deeply. The study results indicate that the Karamat community views the practice of Taukil Wali nikah as a socially and religiously legitimate tradition. However, it often does not follow the officially established order of guardians. This custom is based on the principle of mutual assistance permitted in Islamic law, although normatively, the position of the lineage guardian remains prioritized. This practice shows a shift in the understanding and application of Islamic law at the local level, which can cause conflict in families if not managed properly. This study contributes to the study of Islamic law related to marriage guardianship by highlighting local dynamics and the importance of legal education to maintain harmony between tradition and syariat.